Effect of Supplementation of Vegetable Oils in feed of broiler Rabbits - Arulmuthumathavan, M.; Ramesh, V.; Ramakrishnan, S.; Senthilkumar, S.; Sivakumar, K. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A study was conducted on 48 weaned Soviet Chinchilla rabbits to evaluate the effect of supplementation of vegetable oils with respect to growth and reproductive performance. The rabbits were divided into four groups of twelve each. First group (T1) fed on basal diet alone, second group (T2) fed on basal diet supplemented with rice bran oil @ 2 per cent level, third group (T3) fed on basal diet supplemented with palm oil @2 per cent level and fourth group (T4) fed on basal diet supplemented with both rice bran oil and palm oil each @ one per cent level. The result of the study reveals that rabbits fed basal diet with 2 per cent palm oil group (T3) had significantly (P<0.01) lower cumulative dry matter intake, better average daily and cumulative weight gain, and also feed conversion ratio as compared to other treatment groups. Rabbits supplemented with palm oil 2 per cent level (T3) mated significantly (P<0.01) earlier than other groups. The mean litter size at birth was not significantly differed among treatment groups. The litter size at weaning was significantly higher in T3 and T4. Similarly, litter weight at weaning was significantly (P<0.05) higher in T3 and T4 groups. Higher net income (Rs. 618.29 per animal) was recorded in rabbits supplemented with palm oil alone (T3) group than other groups.